POTENSI PENGENDALIAN TRICHODERMA SPP.TERHADAP GANODERMA SP. DI PERTANAMAN ACACIA MANGIUM UMUR ENAM BULAN - M Mardhiansyah (Universitas Riau, 2011)
The objectives of this study were to ascertain the effectiveness of Trichoderma spp. which was applied innurseries to control Ganoderma sp. in plantations of/I. mangium. Trichoderma spp. Isolates T „ and T „ inpellet form were applied in a ratio of five pellets to each A. mangium seedling, following w il h A. mangiumseedlings which were planted in the field. .At the ages of six months, the level of attack by Ganoderma sp. wascounted at sampling intensity of 100%, and soil samples were taken from around the planting with a samplingintensity of IQ'A in order to identify the presence of isolates T „ and T ^ as well as to identify the soil chemicalproperties. The results of identification through inacro.scopic and microscopic observation as well as dualculture tests, pointed back to isolates which appear to be T „ and T^j. In addition, results of the study showedthat for 6-month old A. mangium, the use of applications of T ^ tead to a tower level of attack by Ganoderma sp.in plantations of A. mangium (0.67%) compared to applications of T „ (1.17%) and the control (0.83%).Grow th of T „ isolate in SA medium up to the sixth day was better (65.49 cm') than that of T,j (36.35cni-).